Zdaňování příjmů fyzických osob v České republice a Irsku - komparace - Segéňová, Daniela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Tato bakalářská práce se zaměřuje na srovnání zdaňování fyzických osob v České republice a v Irsku. Práce obsahuje popis daňových soustav a postupy zdanění fyzických osob v uvedených zemích. V závěru práce jsou uvedeny konkrétní případy zdanění a návrhy pro daňovou optimalizaci vybrané kategorie poplatníků.

This bachelor thesis focuses on a comparison of taxation of individuals in the Czech Republic and Ireland. The thesis contains a description of the tax systems and methods of taxation of individuals in these countries. In conclusion of this thesis there are particular cases of taxation and tax optimization suggestions for selected categories of taxpayers.
Taxation of Incomes of Individuals in the Czech Republic and Ireland - a Comparison
Keywords: Česká republika; daň z příjmů fyzických osob; daňová soustava; Irsko; komparace; zdaňování.; Czech Republic; personal income tax; tax system; Ireland; comparison; taxation.